Cystic fibrosis and pregnancy: counseling, obstetrical management and perinatal outcome. - Grigoriadis, Charalampos; Tympa, Aliki (Investigación Clínica, 2015)
The progress in research of in vitro fertilization and fetal-maternal medicine allows more women and men, with fertility problems due to cystic fibrosis, to have a baby. In the majority of cases, pregnancy in women with cystic fibrosis results in favorable maternal and fetal outcomes. However, the incidence of preterm delivery, intrauterine growth restriction, caesarean section and deterioration of the maternal health are increased. Pre-pregnancy counseling is a crucial component of overall obstetric care, especially in women with poor pulmonary function. Additionally, closer monitoring during pregnancy with a multidisciplinary approach is required. The value of serial ul trasound scans and fetal Doppler assessment is important for the control of maternal and fetal wellbeing, as well as for the definition of the appropriate timing of delivery. In this article, clinical issues of pregnant women with cys tic fibrosis are reviewed; counseling, obstetrical management and perinatal outcomes are being discussed.